Reference Ranges for Corpus Callosum and Cerebellar Vermis Measurements in Fetuses Between 18-36 Weeks of Gestation - Arica, Gorkem; Alpay, Verda; Kaymak, Didem; Alici Davutoglu, Ebru; Madazli, Riza (Gynecology Obstetrics & Reproductive Medicine, 2025)
Objective: To establish gestational age-specific nomograms for the corpus callosum (CC) and cerebellar vermis (CV) using two-dimensional (2D) ultrasound in a Turkish population between 18 and 36 weeks of gestation. Study Design: This cross-sectional study was conducted at the Maternal–Fetal Medicine Unit of a tertiary care centre. A total of 714 low-risk singleton pregnancies between 18+0 and 36+0 weeks of gestation were included. Standardised midsagittal cranial sections were obtained using 2D ultrasound, and measurements were performed by maternal–fetal medicine specialists. Assessed parameters included CC length; thickness of the genu, body, and splenium; and CV anteroposterior (CVAPD) and craniocaudal (CVCCD) diameters. Statistical analysis included descriptive statistics and polynomial regression. Pearson correlation coefficients were calculated to assess the relationship between gestational age and each measurement. Results: Nomograms with 5th, 50th, and 95th percentiles were created for each parameter. All measurements showed significant positive correlations with gestational age (p<0.001). The CC length increased from a mean of 15.96 mm at 18 weeks to 43.12 mm at 36 weeks. The 50th percentile values for CVAPD and CVCCD were 8.91 mm and 10.17 mm at 18 weeks, rising to 20.13 mm and 22.10 mm, respectively, at 36 weeks. Thicknesses of the genu, body, and splenium also showed consistent growth patterns. Conclusion: The nomograms developed in this study provide normative data for fetal midline brain structures and may aid in the prenatal detection of neurodevelopmental abnormalities.